Analisis Pengaruh Investasi, Ekspor dan Tenaga Kerja terhadap PDRB dalam Kawasan Ekonomi Khusus (KEK) di Kabupaten Kotabaru - Rahman, Muhammad Taufiq; Sopiana, Yunita (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research's background is that the particular economic zone policy is expectedto increase investment, exports, and Labor value. With the increase in these three sectors,it will drive economic growth and increase the value of GDP.The benefit of this research is to provide information related to the investment, export,and Labor sectors in contributing to the Kotabaru district GRDP value. And this researchcan understand the regional government, the developer, and community institutionsinterested in developing special economic zones in Mekar Putih, Kotabaru Regency.where this research can be a reference in the preparation of strategic plans in thedevelopment of Special Economic Zones in Mekar Putih Kotabaru RegencyThis research method collects data by retrieving data at the related statistical andservice centers. After that, multiple linear regression analysis was carried out to see theinfluence of independent variables on dependent variables. Software used for regressionanalysis is using EviewsThis study's analysis indicates that investment has a significant effect and has apositive influence on GDP. In contrast, exports and Labor do not have a considerableimpact but still positively influence Kotabaru Regency's GDP.